1990
DOI: 10.1002/eji.1830200933
|View full text |Cite
|
Sign up to set email alerts
|

The neutrophil‐activating proteins interleukin 8 and β‐thromboglobulin: in vitro and in vivo comparison of NH2‐terminally processed forms

Abstract: Isolation of the human neutrophil activating protein (NAP) interleukin 8 (IL8) from leukocytes has revealed that it is structurally related to beta-thromboglobulin (beta TG) from platelets. Both these proteins occur as natural mixtures of multiple forms, differing from each other by unequal truncation at the NH2 terminus. In this study we have compared IL8 and beta TG forms for in vitro and in vivo neutrophil activation. In contrast to IL8, none of the beta TG forms were found to exert granulocyte chemotactic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 28 publications
(5 reference statements)
2
51
1
2
Order By: Relevance
“…More recent findings from our laboratory have indicated that the H. influenzae endotoxin-induced increase in neutrophil chemotaxis can also be blocked by the addition of IL-8 monoclonal neutralizing antibody to the conditioned medium, and suggest that IL-8 is most likely to be involved in this process. This is in agreement with the findings of others, who have also demonstrated that this cytokine primarily influences neutrophil activation [84]. Although others have also demonstrated that epithelial cell derived mediators are chemotactic towards neutrophils [85,86], and indeed other cell types including lymphocytes [87,88] and monocytes [86,89], in vitro, the majority of these studies have employed animal models.…”
Section: Molecular Mechanisms Underlying Endotoxin-induced Proinflammsupporting
confidence: 90%
“…More recent findings from our laboratory have indicated that the H. influenzae endotoxin-induced increase in neutrophil chemotaxis can also be blocked by the addition of IL-8 monoclonal neutralizing antibody to the conditioned medium, and suggest that IL-8 is most likely to be involved in this process. This is in agreement with the findings of others, who have also demonstrated that this cytokine primarily influences neutrophil activation [84]. Although others have also demonstrated that epithelial cell derived mediators are chemotactic towards neutrophils [85,86], and indeed other cell types including lymphocytes [87,88] and monocytes [86,89], in vitro, the majority of these studies have employed animal models.…”
Section: Molecular Mechanisms Underlying Endotoxin-induced Proinflammsupporting
confidence: 90%
“…Both native and chemically synthesized NAP-2 have been shown to induce cytosolic free calcium, elastase release, and chemotaxis in human neutrophils (40,41). Other data indicate that CTAP-I11 is not an attractant; chemotactic activity appears to result from amino terminal cleavage to the CTAP-111 des 1-13 and des 1-15NAP-2 isoforms, which are able to interact with the NAP-I/ IL-8 receptor on human neutrophils (42).…”
Section: Discussionmentioning
confidence: 99%
“…For example, limited NH 2 -terminal truncation of IL-8 (eg, by gelatinase B) enhanced its chemotactic potency, whereas platelet basic protein was found to become chemotactic only when truncated into NAP-2. 21,40 In contrast, small modifications of the NH 2 -terminal residues of MCP-1, MCP-2, and MCP-3 decreased the biologic activity of these CC chemokines. 22,23 Recently, the highly specific protease CD26/DPP IV has been reported to process a number of chemokines at the NH 2 terminus with different effects on their chemotactic and antiviral activities.…”
Section: Discussionmentioning
confidence: 99%
“…Natural IL-8 was purified to homogeneity from conditioned medium of monocytes and contained an equimolar mixture of IL-8(1-77), IL-8(5-77) and IL-8(6-77). 21 Soluble natural human CD26/DPP IV, without membrane anchor and starting at amino acid Gly31, was obtained from total seminal plasma and purified to homogeneity by anion exchange followed by affinity chromatography on immobilized adenosine deaminase as described. 30 Human CXCR3 was stably expressed in Chinese hamster ovary K1 (CHO-K1) cells (American Type Culture Collection [ATCC], Manassas, VA: CCL-61) and the cells were cultured in HAM F-12 medium (Biowhittaker Europe, Verviers, Belgium) supplemented with 10% fetal bovine serum (FBS), 1 mM sodium pyruvate, and 400 g/mL geneticin.…”
Section: Reagents and Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation